2020
DOI: 10.1038/s41598-020-65646-1
|View full text |Cite
|
Sign up to set email alerts
|

Occupational noise exposure and its association with incident hyperglycaemia: a retrospective cohort study

Abstract: noise pollution is reported to be associated with diabetes, but few studies have elucidated the associations between noise frequency characteristics. We aimed to evaluate the relationships between different noise frequency components and incident hyperglycaemia. An industry-based cohort of 905 volunteers was enrolled and followed up to 2012. Octave-band frequencies of workstation noise and individual noise levels were measured in 2012 to classify subjects' exposures retrospectively. We applied Cox regression m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…One study of a population of 3350 adults aged 29–81 years in Switzerland [ 62 ] found positive associations between exposure to night-time road traffic noise and three-month average glycemia. Another study found that subjects exposed to occupational noise levels >80 dBA had a significantly higher risk of hyperglycemia compared with those exposed to <70 dBA [ 63 ]. One birth cohort study [ 64 ] found that exposure to green space was associated with lower maternal blood glucose, and suggested that reduced levels of noise exposure might be a potential mechanism linking green space to maternal blood glucose outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…One study of a population of 3350 adults aged 29–81 years in Switzerland [ 62 ] found positive associations between exposure to night-time road traffic noise and three-month average glycemia. Another study found that subjects exposed to occupational noise levels >80 dBA had a significantly higher risk of hyperglycemia compared with those exposed to <70 dBA [ 63 ]. One birth cohort study [ 64 ] found that exposure to green space was associated with lower maternal blood glucose, and suggested that reduced levels of noise exposure might be a potential mechanism linking green space to maternal blood glucose outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Further, more than 1.1 million workers were exposed to noise at levels above the daily occupational exposure limit (85 dB) in Australia [19]. Apart from hearing loss, noise can contribute to a series of health problems such as metabolic syndromes [20][21][22], cardiovascular disease [23,24], sleep prob-…”
mentioning
confidence: 99%
“…The study showed a signi cant relationship between occupational noise exposure and incident hyperglycemia (Relative Risk 1.80 [95% CI 1.04-3.10]) 27 . However, this study focused on hyperglycemiawhich includes impaired fasting glucose-and did not re ect co-exposure factors and time-varying lifestyle factors.…”
Section: Discussionmentioning
confidence: 98%